Magnetic beads and method for producing magnetic beads

Magnetic beads with controlled particle size and silicon oxide coating address the aggregation and settling issues of conventional beads, enhancing extraction efficiency and reducing PCR test duration.

JP7625936B2Active Publication Date: 2025-02-04SEIKO EPSON CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021057443
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-30
Publication Date
2025-02-04
Estimated Expiration
2041-03-30

AI Technical Summary

Technical Problem

Conventional magnetic beads used in PCR methods and cell tests suffer from insufficient extraction efficiency due to oversized particles that aggregate and settle, leading to prolonged inspection times and reduced test efficiency.

Method used

Magnetic beads with a specific particle size distribution (D50 of 0.1 to 1.5 μm and D90/D50 ratio of 2.00 or less) and a coating layer, such as silicon oxide, are produced using a high-pressure water atomization method and wet classification to ensure uniform distribution and high extraction efficiency.

Benefits of technology

The beads achieve improved extraction efficiency, reduced CT values, and faster nucleic acid extraction processes by minimizing aggregation and sedimentation, thereby shortening testing time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007625936000001
    Figure 0007625936000001
  • Figure 0007625936000002
    Figure 0007625936000002
Patent Text Reader

Abstract

To provide magnetic beads capable of ensuring sufficient extraction of an inspection target substance and preventing reduction in redispersibility and sedimentability due to particle agglomeration, and a manufacturing method therefor.SOLUTION: A magnetic bead provided herein comprises metal magnetic powder and a coating layer coating a surface of the metal magnetic powder. A 50% particle diameter D50 of the metal magnetic powder in a particle size distribution is 0.1-1.5 μm, and a ratio D90 / D50 of a 90% particle diameter D90 of the metal magnetic powder to the 50% particle diameter D50 in the particle size distribution is 2.00 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to magnetic beads and a method for producing magnetic beads. [Background technology]

[0002] In recent years, magnetic separation methods using minute magnetic beads have been widely used in diagnosis and various tests in the medical field, for example, in PCR for extracting biological materials and in cell testing.

[0003] The PCR method is a method of extracting nucleic acid and specifically amplifying and detecting it. In order to efficiently extract this nucleic acid, recent PCR methods use magnetic beads that can hold nucleic acid and extract the nucleic acid by applying a magnetic field. Specifically, the target substance is extracted by repeatedly applying the magnetic field on and off multiple times. A similar method is also used in the field of cell testing, such as for the extraction of cancer cells. Various types of magnetic beads have been investigated so far.

[0004] For example, Patent Document 1 describes magnetic beads having an average particle size of 0.5 μm to 10 μm, in which a silica film is applied to amorphous magnetic powder.

[0005] Moreover, Patent Document 2 discloses magnetic silica particles having a structure in which metal particles and ceramic particles having an average particle size of 0.2 to 10 μm are mixed.

[0006] Patent Document 3 discloses metal microparticles and magnetic beads having a 50% particle size (volume-based median diameter (d50)) of 0.1 μm to 10 μm and a 90% particle size (volume-based 90% accumulated particle size (d90)) of 0.15 to 15 μm. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2017-176023 A [Patent Document 2] JP 2007-224323 A [Patent Document 3] International Publication No. 2007 / 148734 Summary of the Invention [Problem to be solved by the invention]

[0008] Combined with the recent increase in demand for PCR testing, there is a demand in the medical field for diagnostics and various tests to shorten testing times and improve the efficiency of extracting test subjects.

[0009] However, there are cases where the magnetic beads described in Patent Documents 1 to 3 are unable to ensure a sufficient amount of extraction of the target substance, which results in a long test time and a risk of reduced test efficiency.

[0010] In addition, conventional magnetic beads are often classified by dry classifiers such as rotary classifiers using centrifugal force, and the particle size distribution of the obtained magnetic beads often contains coarse particles that are very large compared to the average particle size. Such coarse particles have high magnetization in a magnetic field, so they attract surrounding particles and aggregate, and even when the magnetic field is turned off, the dispersibility is lost and significant aggregation occurs. Furthermore, when the particles aggregate, they may settle to the bottom of the reagent due to their own weight. As a result, the extraction efficiency of the test target substance is reduced, and the test time is extended accordingly. [Means for solving the problem]

[0011] In order to solve the above problems, one embodiment of the magnetic beads of the present invention is a magnetic bead having a magnetic metal powder and a coating layer that covers the surface of the magnetic metal powder, wherein the 50% particle diameter D50 of the magnetic metal powder in the particle size distribution is 0.1 to 1.5 μm, and the ratio D90 / D50 of the 90% particle diameter D90 of the magnetic metal powder in the particle size distribution to the 50% particle diameter D50 is 2.00 or less.

[0012] A method for producing magnetic beads according to one embodiment of the present invention includes a magnetic metal powder preparation step of obtaining magnetic metal powder, a submerged classification step of classifying the magnetic metal powder in a liquid to extract magnetic metal powder having a 50% particle diameter D50 of 0.1 to 1.5 μm and a D90 / D50 ratio, which is the ratio of the 90% particle diameter D90 of the magnetic metal powder to the 50% particle diameter D50 in the particle size distribution, of 2.00 or less, and a coating step of forming a coating layer on the magnetic metal powder. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, magnetic beads and a method for producing the same according to one embodiment of the present invention will be described.

[0014] [Magnetic beads] The magnetic beads according to this embodiment are magnetic beads having a magnetic metal powder and a coating layer that coats the surface of the magnetic metal powder, and the 50% particle diameter D50 of the magnetic metal powder in the particle size distribution is 0.1 to 1.5 μm, and the ratio D90 / D50 of the 90% particle diameter D90 of the magnetic metal powder in the particle size distribution to the 50% particle diameter D50 is 2.00 or less.

[0015] The magnetic beads according to the present embodiment are a particle group capable of adsorbing biological materials such as nucleic acids such as DNA and cells, and have magnetic metal powder and a coating layer that coats the surface of the magnetic metal powder. For example, when extracting nucleic acids, powdered magnetic beads are used.

[0016] <Magnetic metal powder> The magnetic metal powder is a particle having magnetism. The magnetic metal powder is preferably a magnetic metal particle containing at least one of Fe, Co, and Ni. In particular, from the viewpoint of obtaining high saturation magnetization, it is preferable to increase the Fe content in the composition of the magnetic metal powder, and more preferably to make the composition mainly composed of Fe. More preferably, Fe is 70% or more in atomic ratio. The magnetic metal powder may be pure Fe consisting of only Fe. The composition of the magnetic metal powder may also be an alloy mainly composed of Fe (Fe-based alloy), and examples thereof include an Fe-Co-based alloy, an Fe-Ni-based alloy, an Fe-Co-Ni-based alloy, or a compound containing Fe, Co, and Ni.

[0017] The Fe-based alloy may contain, in addition to the above-mentioned elements such as Co and Ni that exhibit ferromagnetic properties by themselves, one or more elements selected from the group consisting of Cr, Nb, Cu, Al, Mn, Mo, Si, Sn, B, C, P, Ti, and Zr, depending on the desired properties. The Fe-based alloy may contain unavoidable impurities within a range that does not impair the effects of the present invention.

[0018] In the present embodiment, the unavoidable elements are elements (impurities) that are unintentionally mixed into the raw materials of the magnetic metal powder or the magnetic beads during production. The unavoidable elements are not particularly limited, but examples thereof include O, N, S, Na, Mg, and K.

[0019] The structure constituting the magnetic metal powder is not particularly limited, and can take various forms such as a crystalline structure, an amorphous structure, a nanocrystalline structure, etc. From the viewpoint of obtaining high magnetization, the magnetic metal powder is preferably a carbonyl iron powder consisting essentially of 100 mass % Fe, an Fe-Si alloy powder, an Fe-Si-Cr alloy powder, or the like.

[0020] On the other hand, the magnetic beads of this embodiment are required to exhibit high dispersibility in the extraction process of nucleic acids, cells, etc. From the viewpoint of obtaining this high dispersibility, it is preferable that the coercive force (Hc) of the magnetic metal powder is low. As the structure of the magnetic metal powder that can realize a low coercive force, an amorphous structure or a nanocrystalline structure is preferable. In particular, an amorphous structure has a relatively high electric resistance value and a small coercive force because the atomic arrangement is irregular. Therefore, the magnetic beads made of magnetic metal powder with an amorphous structure are less likely to aggregate with each other when a magnetic field (magnetic field) is not applied, and can be uniformly dispersed in the test solution. Furthermore, even if the application of a magnetic field is repeatedly turned on and off, the redispersibility is excellent, so that the aggregation of the beads can be further suppressed.

[0021] In order to obtain an amorphous structure and a nanocrystalline structure, it is effective to increase the quenching rate during solidification during the production of the magnetic metal powder. The ease of forming an amorphous structure and a nanocrystalline structure also depends on the alloy composition.

[0022] A specific alloy system suitable for forming an amorphous structure or a nanocrystalline structure is preferably a composition containing Fe and one or more elements selected from the group consisting of Cr, Si, B, C, P, Nb, and Cu.

[0023] The composition ratio of the magnetic metal powder can be determined, for example, by ICP emission spectrometry as specified in JIS G 1258:2014, spark emission spectrometry as specified in JIS G 1253:2002, etc. Examples of the analysis device include a solid-state optical emission spectrometer (spark optical emission spectrometer, model: SPECTROLAB, type: LAVMB08A) manufactured by SPECTRO, and an ICP device (CIROS120 type) manufactured by Rigaku Corporation. In addition, when quantifying the C content, the oxygen stream combustion (high-frequency induction heating furnace combustion)-infrared absorption method as specified in JIS G 1211:2018 can be particularly applied. Examples of the carbon content analysis device include a carbon-sulfur analyzer (CS200 type) manufactured by LECO.

[0024] In addition, to determine whether the structure of the magnetic metal powder is amorphous, it is advisable to use X-ray diffraction. If no clear diffraction peaks are observed by X-ray diffraction, the structure can be determined to be amorphous.

[0025] Regarding the average particle size of the magnetic metal powder of this embodiment, the 50% particle size D50 in the particle size distribution is 0.1 μm to 1.5 μm. If the 50% particle size D50 is less than 0.1 μm, the magnetic properties per particle become excessively small, and the extraction efficiency of the magnetic beads decreases. Therefore, the 50% particle size D50 of the magnetic metal powder is set to 0.1 μm or more. In this way, by setting the 50% particle size D50 of the magnetic metal powder to 0.1 μm or more, it is possible to obtain magnetic properties sufficient for performing the extraction and recovery operation of the test target substance using a magnetic field at high speed. For these reasons, the 50% particle size D50 is more preferably 0.3 μm or more, and even more preferably 0.5 μm or more.

[0026] On the other hand, if the 50% particle diameter D50 of the magnetic metal powder exceeds 1.5 μm and becomes coarse, it is not possible to secure a sufficient specific surface area, and there is a risk that the test target substance such as nucleic acid cannot be sufficiently extracted. In addition, if the 50% particle diameter D50 of the magnetic metal powder becomes excessively large, the weight per particle increases, so that it precipitates at an early stage of the test. As a result, the magnetic metal powder that contributes to the extraction of the test target substance decreases, and the extraction efficiency decreases. Therefore, the 50% particle diameter D50 of the magnetic metal powder is set to 1.5 μm or less. In this way, by setting the 50% particle diameter D50 of the magnetic metal powder to 1.5 μm or less, it is possible to increase the amount of the test target substance to be extracted, and for example, to reduce the Ct (Threshold Cycle) value during PCR testing. The "Ct value" is the cycle number (thermal cycle number) when the amplified product by PCR testing reaches a certain amount and the fluorescent brightness reaches a certain value or more. For these reasons, the 50% particle size D50 of the magnetic metal powder is more preferably 1.2 μm or less, and even more preferably 1.0 μm or less.

[0027] Furthermore, the magnetic metal powder of this embodiment has a ratio D90 / D50 of 2.00 or less, which is the ratio of the 90% particle diameter D90 to the 50% particle diameter D50 in the particle size distribution. The 90% particle diameter D90 is the particle diameter at which the integrated value is 90% in the integrated distribution curve obtained from the measurement results of the particle size distribution. In other words, the 90% particle diameter D90 is an index that represents the size of coarse particles mixed in the magnetic metal powder. In this embodiment, when defining the particle size distribution of the magnetic metal powder, D90 / D50, which is the ratio of the particle size of the coarse particles to the 50% particle size D50, which is the average particle size, is used, and this D90 / D50 is set to 2.00 or less. When D90 / D50 is greater than 2.00, the particle size distribution is one in which a large amount of coarse particles are mixed in with respect to the average particle size (D50). Since coarse particles have high magnetism in a magnetic field, when a large amount of coarse particles are mixed in, they will aggregate while attracting surrounding particles, and even if the magnetic field is turned off, dispersibility will be lost and significant aggregation will occur. Furthermore, when the particles aggregate, they will settle to the bottom of the reagent due to their own weight, which may lead to a decrease in extraction efficiency and an increase in the test time associated with it. Therefore, D90 / D50 is set to 2.00 or less, more preferably 1.75 or less, and even more preferably 1.55 or less.

[0028] The 50% particle diameter D50 and the 90% particle diameter D90 can be determined, for example, from a cumulative distribution curve obtained by measuring the volumetric particle size distribution by a laser diffraction / dispersion method. Specifically, in the cumulative distribution curve, the particle diameter at which the cumulative value is 50% from the small diameter side is the 50% particle diameter D50 (median diameter), and the particle diameter at which the cumulative value is 90% from the small diameter side is the 90% particle diameter D90.

[0029] The shape of the magnetic metal powder in this embodiment is not particularly limited, and may be a circular, elliptical or polygonal cross-sectional shape. From the viewpoint of suppressing powder aggregation and improving the mobility of the magnetic metal powder, it is preferable that the ratio of particles with a circularity of 0.60 or less in the magnetic metal powder is 2.0% or less. If the particles with a circularity of 0.60 or less exceed 2.0%, the density of the magnetic field lines formed by the magnetized particles becomes non-uniform due to the contribution of shape magnetic anisotropy, and as a result, the aggregation of the magnetic metal powder becomes significant. Furthermore, such aggregation reduces the mobility of the magnetic metal powder. The circularity of the magnetic metal powder is defined by the following formula.

[0030] Circularity = 4πS / L 2 (1) In the above formula, S represents the projected area of ​​the particle, and L represents the circumferential length of the particle.

[0031] The circularity of the magnetic metal powder can be measured by the following image processing. By processing images of multiple magnetic metal powder particles taken with a scanning electron microscope (SEM) or optical microscope, the area and perimeter of each powder particle can be calculated. Furthermore, the ratio of powder particles having a specific circularity among multiple powder particles can also be calculated. Specifically, for example, the projected area, perimeter, and ratio can be measured using the image processing system "Image-J" (National Institutes of Health, USA).

[0032] In addition, the saturation magnetization of the magnetic metal powder in this embodiment is preferably 1.1 T or more. The "saturation magnetization" is the value of magnetization that becomes saturated when the applied magnetic field is strong. Therefore, the larger the saturation magnetization of the magnetic metal powder, the more fully it can function as a magnetic material, and the movement speed (recovery speed) after extraction in the magnetic field can be improved. As a result, the inspection time can be shortened. In order to obtain such an effect, the saturation magnetization of the magnetic metal powder is preferably 1.1 T or more, and more preferably 1.2 T or more. The upper limit of the saturation magnetization of the magnetic metal powder is not particularly limited, and may be 2.2 T or less from the viewpoint of ease of material selection suitable for the balance between performance and cost.

[0033] The saturation magnetization of the magnetic metal powder can be measured by a vibrating sample magnetometer (VSM). Specifically, it can be measured by a "TM-VSM1230-MHHL" manufactured by Tamagawa Seisakusho Co., Ltd.

[0034] In addition, the coercive force Hc of the magnetic metal powder in this embodiment is preferably 1500 A / m or less. The term "coercive force Hc" refers to the value of the external magnetic field in the opposite direction required to return a magnetized magnetic body to an unmagnetized state. In other words, the coercive force Hc means the resistance to external magnetization. The smaller the coercive force Hc of the magnetic metal powder, the less likely the beads are to aggregate even when switching from a state in which a magnetic field (magnetic field) is applied to a state in which it is not applied, and the beads can be uniformly dispersed in the test solution. Furthermore, even when the application of a magnetic field is repeatedly switched, the smaller the coercive force Hc, the better the redispersibility of the magnetic metal powder is, so that the aggregation of the beads can be further suppressed. In order to obtain such an effect, the coercive force Hc of the magnetic metal powder is preferably 1500 A / m or less, and more preferably 800 A / m or less. The lower limit of the coercive force Hc of the magnetic metal powder is not particularly limited, and may be 5 A / m or more from the viewpoint of ease of material selection suitable for the balance between performance and cost.

[0035] Although the magnetic metal powder has been described above, the method for producing the magnetic metal powder constituting the magnetic beads of the present embodiment is not particularly limited, and the production method may be selected according to the desired composition and form. For example, the magnetic metal powder is preferably an Fe-based metal alloy powder produced by an atomization method that easily obtains spherical powder.

[0036] <Coating layer> The coating layer is formed on the surface of the magnetic metal powder. The coating layer may be formed on at least a part of the surface of the magnetic metal powder, but is preferably formed so as to cover the entire surface.

[0037] The coating layer of the present embodiment may be any material that can impart the extraction performance (adsorption performance) of a test substance such as nucleic acid. Examples of materials that can sufficiently exhibit such performance include silicon oxide. Silicon oxide is, for example, SiOx (0 < x ≤ 2), and specifically, SiO2 is preferred. Silicon oxide enables the extraction and recovery of nucleic acid by specifically adsorbing nucleic acid in an aqueous solution in which a chaotropic substance is present. A "chaotropic substance" is a substance that has an effect of increasing the water solubility of hydrophobic molecules by generating chaotropic ions (monovalent anions with a large ionic radius) in an aqueous solution and contributes to nucleic acid adsorption. Specific examples of chaotropic substances include guanidine hydrochloride, sodium iodide, sodium perchlorate, and the like.

[0038] The coating layer may also include a composite oxide or composite of silicon and one or more elements selected from the group consisting of Al, Ti, V, Nb, Cr, Mn, and Zr. These elements Al, Ti, V, Nb, Cr, Mn, and Zr are elements with excellent resistance to elution, which suppresses ion elution from the magnetic metal powder to be coated. Therefore, by using a composite oxide or composite of at least one of these elements and silicon as the coating layer, it is possible to improve the extraction performance of the test substance while ensuring resistance to elution. The coating layer may also be formed of multiple layers made of oxides of different elements. Furthermore, a coating layer that can achieve the same effect may be formed of an inorganic substance such as silicate, or an organic substance such as organic siloxane and phosphonic acid.

[0039] The coating layer may contain unavoidable impurities within a range that does not impair the effects of the present invention. For example, when silicon oxide is used as the coating layer, examples of the unavoidable impurities in the silicon oxide include C, N, and P.

[0040] The average thickness of the coating layer is preferably 1 nm to 100 nm. If the average thickness of the coating layer is less than 1 nm, the elution of ions from the magnetic metal powder to be coated cannot be sufficiently suppressed, and the extraction performance of the magnetic metal powder is impaired. On the other hand, if the average thickness of the coating layer exceeds 100 nm, the extraction performance of the test target substance is saturated and the manufacturing cost increases. Therefore, it is more preferable that the average thickness of the coating layer is 3 nm to 50 nm.

[0041] The thickness of the coating layer can be measured, for example, from a cross-sectional observation image by a transmission electron microscope (TEM). In this embodiment, the thickness of each coating layer is measured for 10 or more particles, and the average value is calculated. The thickness of the coating layer of each particle is measured at 5 or more points per particle, and the average value is calculated.

[0042] The configuration of the coating layer can be confirmed by, for example, EDX analysis, Auger electron spectroscopy, etc. For example, the configuration of the coating layer can be confirmed by measuring the composition distribution in the radial direction of the particle by EDX analysis of the formed coating layer.

[0043] In the magnetic beads of the present embodiment, the coating layer is formed on at least a part of the surface of the magnetic metal powder. With this configuration, it is possible to improve the amount and efficiency of extraction of the test target substance, and thereby shorten the test time.

[0044] According to the magnetic beads described above, by setting the average particle size (D50) and particle size distribution (D90 / D50) of the magnetic metal powder within an appropriate range, it is possible to improve the amount and efficiency of the extracted substance to be tested, and also to reduce the Ct value during PCR testing. Furthermore, by setting the particle size distribution to reduce the proportion of coarse particles, it is possible to significantly suppress particle aggregation and sedimentation, and further improve the redispersibility of the particles.

[0045] [Magnetic bead manufacturing method] Next, a method for producing the above magnetic beads will be described. The method for manufacturing magnetic beads according to this embodiment includes a magnetic metal powder production process for obtaining magnetic metal powder, a submerged classification process for classifying the magnetic metal powder in liquid to extract magnetic metal powder having a 50% particle diameter D50 of 0.1 to 1.5 μm and a D90 / D50 ratio, which is the ratio of the 90% particle diameter D90 of the magnetic metal powder to the 50% particle diameter D50 in the particle size distribution, of 2.00 or less, and a coating process for forming a coating layer on the magnetic metal powder.

[0046] <Magnetic metal powder manufacturing process> First, magnetic metal powder is prepared. The magnetic metal powder is formed by using the above-mentioned magnetic metal powder material, for example, by various powdering methods such as atomization (for example, water atomization, gas atomization, high-speed rotating water flow atomization, etc.) and pulverization. Among them, it is preferable to use the atomization method because it is easy to obtain spherical powder.

[0047] Atomization methods are classified into water atomization, high-pressure water atomization, high-speed rotating water flow atomization, gas atomization, etc., depending on the type of coolant and the device configuration. The atomization method is a method for producing metal powder (amorphous alloy powder) by colliding molten metal (molten metal) with a fluid (liquid or gas) sprayed at high speed, pulverizing it and cooling it. By producing amorphous alloy powder using this type of atomization method, extremely fine powder can be produced efficiently. Furthermore, the particle shape of the amorphous alloy powder becomes close to spherical due to the action of surface tension.

[0048] Among these, in the high-pressure water atomization method, the molten metal is first split in the air by a large negative pressure to form fine molten metal droplets. These fine molten metal droplets are then rapidly cooled and solidified by a high-speed water jet to obtain rapidly cooled fine powder that is nearly spherical. Therefore, the high-pressure water atomization method is the most suitable method for producing magnetic metal powder. In addition, since the molten metal can be cooled extremely quickly, the disordered atomic arrangement in the molten metal can be maintained to a high degree during solidification. Therefore, amorphous alloy powder with a particularly high degree of amorphization (alloy powder that is more reliably amorphous) can be efficiently produced. Therefore, the high-pressure water atomization method is preferable as a method for forming magnetic metal powder.

[0049] After the magnetic metal powder production process, a submerged classification process or a coating process is performed. That is, in this embodiment, the order of the submerged classification process and the coating process does not matter, and after the magnetic metal powder production process, the submerged classification process may be performed before the coating process, or the coating process may be performed before the submerged classification process. The following describes a case where the coating step is carried out after the magnetic metal powder production step and then the submerged classification step.

[0050] <Liquid classification process> In this embodiment, by classifying the magnetic metal powder in a liquid, a magnetic metal powder having a 50% particle size D50 of 0.1 to 1.5 μm and a D90 / D50 of 2.00 or less can be obtained. In order to obtain a magnetic metal powder having such a desired particle size and particle size distribution, the classification is performed in a liquid, that is, a so-called wet classification. While the dry classification classifies particles by utilizing the difference in mechanical behavior in an air stream, the wet classification performed in a liquid classifies particles by centrifugal force, gravity, or the like in the liquid. Therefore, the wet classification performed in a liquid can classify particles with high accuracy even at sizes on the order of submicrons, and the aggregation of particles during classification can be suppressed more than in the dry classification.

[0051] Specifically, the submerged classification step is preferably performed by centrifugal force or gravity. High classification accuracy can be obtained in either a centrifugal field or a gravitational field. From the viewpoint of more precise classification, classification by gravity is preferred.

[0052] Gravity classification is a classification method that utilizes the fact that the settling speed in liquid differs depending on the particle size (particle diameter), and for example, an upright cylindrical wet classifier can be used. In addition, the settling speed for each particle size (particle diameter) is calculated in advance, and powder is collected from the classifier according to the settling time, thereby obtaining metal powder with a desired particle diameter. Note that a dispersant such as a carboxylic acid may be used to suppress the aggregation of particles in the liquid.

[0053] <Coating process> After the submerged classification process, a coating layer is formed on the surface of the magnetic metal powder. The method of forming the coating layer is not particularly limited as long as it is a method that realizes the above-mentioned material and average thickness of the coating layer. For example, a wet formation method such as a sol-gel method, an ALD (Atomic Layer Deposition), a CVD (Chemical Vapor Deposition), an ion plating, or other dry formation methods can be mentioned. When the coating layer is a silicon oxide film, among these, the Stöber method, which is a type of sol-gel method, can be used.

[0054] The Stober process is a method for forming monodisperse particles by hydrolysis of metal alkoxide. When the coating layer is made of silicon oxide, it is obtained by hydrolysis reaction of silicon alkoxide using the Stober process.

[0055] Specifically, first, the magnetic metal powder is dispersed in an alcohol solution containing silicon alkoxide. Examples of the alcohol solution include lower alcohols such as ethanol and methanol. The ratio of silicon alkoxide to alcohol is, for example, 10 to 50 parts by weight of alcohol mixed with 1 part by weight of tetraethoxysilane. In order to achieve a uniform coating on the particle surface, the ratio of the magnetic metal powder to the silicon alkoxide is preferably 0.01 to 0.1 parts by weight of silicon alkoxide mixed with 1 part by weight of magnetic metal powder. In addition, it is preferable to use TEOS (tetraethoxysilane, Si(OC2H5)4) as the silicon alkoxide.

[0056] Next, ammonia water is supplied as a catalyst to promote the reaction, causing hydrolysis, which causes a dehydration condensation reaction between the hydrolyzates and between the hydrolyzates and silicon alkoxide, forming -Si-O-Si- bonds on the particle surface, forming a silicon oxide film.

[0057] In addition, it is preferable to stir the magnetic metal powder and the alcohol solution using an ultrasonic wave application device before and after supplying the ammonia water. By carrying out stirring in each step in this manner, it is possible to promote uniform dispersion of the particles and to form a uniform silicon oxide film on the particle surface. It is preferable to carry out stirring for a time period that is sufficient for the hydrolysis reaction of the silicon alkoxide to proceed sufficiently.

[0058] In the above, the magnetic metal powder is dispersed in an alcohol solution containing silicon alkoxide, and then ammonia water is supplied, but this is not limited to the above. For example, the alcohol solution in which the magnetic metal powder is dispersed may be mixed with ammonia water, and then the alcohol solution containing silicon alkoxide may be mixed. In this case, the alcohol solution containing silicon alkoxide may be added in several portions. When adding in several portions, the above-mentioned stirring may be performed for each addition, or the alcohol solution may be added to the solution being stirred.

[0059] The thickness of the coating layer is also affected by the ratio of silicon alkoxide in the solution. That is, if the ratio of silicon alkoxide in the solution is increased, the thickness of the coating layer increases, but if the ratio is increased too much, there is a risk that excessive silica will be formed alone. Therefore, the ratio of silicon alkoxide in the solution is adjusted to obtain the desired thickness of the coating layer.

[0060] The magnetic beads of this embodiment can be manufactured by the above steps, but the obtained magnetic beads may be subjected to a heat treatment to further improve the performance. For example, by drying and baking at 60 to 120°C for 10 to 300 minutes, it is possible to remove hydrates remaining in the beads and improve the strength of the beads.

[0061] In addition, in the manufacturing method of the magnetic beads of this embodiment, a classification step may be further carried out between the magnetic metal powder production step and the submerged classification step. That is, after the magnetic metal powder is produced by the magnetic metal powder production step, most of the coarse particles are classified and removed by a dry or wet method, and then the submerged classification is carried out, thereby making it possible to further improve the classification accuracy. EXAMPLES

[0062] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.

[0063] Alloy powders (magnetic metal powders) were prepared by high-pressure water atomization from alloys having the compositions shown in Table 1. The obtained alloy powders were classified by the classification methods shown in Table 1.

[0064] The conditions for gravity classification in liquid in Example 1 will be described. First, 30 g of the alloy powder with an average particle size (D50) of about 3 μm was dispersed in 400 mL of pure water by ultrasonic waves to prepare a raw powder dispersion. Next, this raw powder dispersion was slowly poured into 1600 mL of pure water to make a slurry, which was then left to stand for 330 minutes and classified. After that, 600 mL of the slurry was collected from the liquid surface using a siphon. The collected slurry was heated and dried at 85°C for 120 minutes to evaporate the water and obtain a powder.

[0065] Next, the conditions for centrifugal classification in liquid in Example 2 will be described. As in Example 1, the alloy powder having an average particle size of about 3 μm was dispersed in water at a weight content of 7%, and the dispersion was classified using a wet rotary classifier to obtain a dispersion containing powder having the average particle size shown in the table. This was then dried by heating at 85° C. for 120 minutes to obtain a powder.

[0066] In the other examples shown in the table, the submerged gravity classification and the submerged centrifugal classification were carried out in the same manner as in Examples 1 and 2, respectively.

[0067] In the air classification in Comparative Examples 1 and 2, the alloy powders having average particle sizes of about 10 μm and about 3 μm, respectively, were classified by a cyclone classifier, and the classification point was adjusted to obtain powders.

[0068] After classification, the alloy powder was measured for D50, D90, D90 / D50, and the proportion of beads having a circularity of 0.60 or less by the same methods as above. The results are shown in Table 2.

[0069] Next, a silicon oxide (SiO2) film (average thickness: about 20 nm) was formed on the surface of the classified alloy powder by the following method to obtain magnetic beads.

[0070] First, 100 g of alloy powder sample was dispersed and mixed in 950 mL of ethanol, and the mixture was stirred for 20 minutes using an ultrasonic applicator. After stirring, a mixed solution of 30 mL of pure water and 180 mL of ammonia water was added and stirred for another 10 minutes. Then, a mixed solution of 3.3 mL of tetraethoxysilane and 100 mL of ethanol was further added and stirred for 120 minutes to form a silicon oxide film on the surface of the alloy powder, and magnetic beads were produced. The magnetic beads were washed with ethanol and acetone, respectively, and then dried at 65°C for 30 minutes and baked at 200°C for 90 minutes.

[0071] The magnetic beads obtained by the above method were evaluated for Ct value, redispersibility, and the presence or absence of sedimentation (sedimentation property).In addition, the magnetic properties (coercive force and saturation magnetization) of the obtained magnetic beads were measured by a vibrating sample magnetometer (VSM).

[0072] The Ct value is the cycle number in PCR when a certain amount of amplified product is reached and the fluorescent brightness reaches or exceeds a certain value. In other words, the smaller the Ct value (the fewer the cycle number), the higher the extraction efficiency of the substance being tested and the shorter the testing time can be achieved. In this example, the magnetic beads were first used to carry out a conventional nucleic acid extraction reaction (pretreatment), and the extract was added to a PCR reaction solution to carry out a real-time PCR reaction to determine the Ct value. PCR was carried out under the same conditions for each magnetic bead using E. coli DNA as the target nucleic acid.

[0073] Regarding redispersibility, the redispersibility of the magnetic beads was visually evaluated after the application of a magnetic field was repeated seven times as a nucleic acid extraction step. As for sedimentation properties, the presence or absence of sedimentation 30 minutes after the stirring treatment in the nucleic acid extraction process was also visually evaluated.

[0074] The above evaluation results are shown in Table 2. As shown in Table 2, it was confirmed that the magnetic properties were excellent in both the magnetic beads of Examples 1 and 2. In addition, the magnetic beads of Examples 1 and 2 both had smaller Ct values ​​than the comparative example, and were excellent in both redispersibility and sedimentation properties, confirming that the extraction speed and extraction efficiency of nucleic acid were significantly improved.

[0075] [Table 1]

[0076] [Table 2]

Claims

1. A magnetic bead having a magnetic metal powder and a coating layer that coats the surface of the magnetic metal powder, The magnetic metal powder has a 50% particle diameter D50 of 0.1 to 1.5 μm in particle size distribution; The ratio D90 / D50 of the 90% particle diameter D90 to the 50% particle diameter D50 of the magnetic metal powder in the particle size distribution is 2.00 or less, The magnetic metal powder has a coercive force Hc of 1500 A / m or less and a saturation magnetization of 1.1 T or more. A magnetic bead characterized by:

2. 2. The magnetic beads according to claim 1, wherein the ratio of particles having a circularity of 0.60 or less in the magnetic metal powder is 2.0% or less.

3. 3. The magnetic beads according to claim 1, wherein the magnetic metal powder is an Fe-based alloy powder produced by an atomization method.

4. The magnetic beads according to any one of claims 1 to 3, characterized in that the coating layer is made of silicon oxide or a composite oxide of silicon and one or more elements selected from the group consisting of Al, Ti, V, Nb, Cr, Mn and Zr.

5. 5. The magnetic bead according to claim 1, wherein the coating layer has a thickness of 1 nm to 100 nm.

6. a magnetic metal powder producing step for obtaining magnetic metal powder; a liquid classification process for classifying the magnetic metal powder in a liquid to extract magnetic metal powder having a 50% particle diameter D50 of 0.1 to 1.5 μm and a ratio D90 / D50 of the 90% particle diameter D90 of the magnetic metal powder to the 50% particle diameter D50 in a particle size distribution of 2.00 or less; A coating step of forming a coating layer on the magnetic metal powder; having A method for producing magnetic beads, wherein the magnetic metal powder has a coercive force Hc of 1500 A / m or less and a saturation magnetization of 1.1 T or more.

7. 7. The method for producing magnetic beads according to claim 6, wherein the submerged classification step classifies the magnetic beads by centrifugal force or gravity.

8. 8. The method for producing magnetic beads according to claim 7, wherein in the magnetic metal powder producing step, the magnetic metal powder is produced by an atomization method.

9. The method for producing magnetic beads described in claim 7 or 8, characterized in that the coating layer is made of silicon oxide or a composite oxide of silicon and one or more elements selected from the group consisting of Al, Ti, V, Nb, Cr, Mn and Zr.

10. 10. The method for producing magnetic beads according to claim 7, wherein in the coating step, the coating layer is formed to a thickness of 1 nm to 100 nm.

11. The method for producing magnetic beads according to any one of claims 7 to 10, characterized in that a dispersant is used in the submerged classification step.

12. 12. The method for producing magnetic beads according to claim 7, further comprising a classification step between the magnetic metal powder production step and the submerged classification step.

Citation Information

Patent Citations

  • Manufacturing method of soft magnetic material

    JP2006049625A

  • Magnetic silica particle and method for producing the same

    JP2007224323A

  • Metallic microparticle, manufacturing method therefor, and magnetic bead

    JP2010156054A

  • Core for reactor, method of manufacturing the same, and reactor

    JP2012238866A

  • Nucleic acid-binding solid phase carrier and nucleic acid extraction method

    JP2017176023A